Isolated Retroperitoneal Hydatid Cyst Invading Splenic Hilum - Safak Ozturk; Mutlu Unver; Burcin Kibar Ozturk; Eyup Kebapci; Osman Bozbiyik; Varlık Erol; Nihat Zalluhoglu; Mustafa Olmez (Case Reports in Surgery)
Introduction. Hydatid disease (HD) is an infestation that is caused by the larval stage of Echinococcus granulosus. The liver is affected in approximately two-thirds of patients, the lungs in 25%, and other organs in a small proportion. Primary retroperitoneal hydatid cyst is extremely rare. The most common complaint is abdominal pain; however, the clinical features of HD may be generally dependent on the location of the cyst. Case Presentation. A 43-year-old female was admitted with the complaint of abdominal pain. Her physical examination was normal. Computed tomography (CT) revealed a 17 × 11 cm cystic lesion, with a thick and smooth wall that is located among the left liver lobe, diaphragm, spleen, tail of the pancreas, and transverse colon and invading the splenic hilum. Total cystectomy and splenectomy were performed. Pathological examination was reported as cyst hydatid. Discussion. Cysts in the peritoneal cavity are mainly the result of the spontaneous or traumatic rupture of concomitant hepatic cysts or surgical inoculation of a hepatic cyst. Serological tests contribute to diagnosis. In symptomatic and large hydatid peritoneal cysts, surgical resection is the only curative treatment. Total cystectomy is the gold standard. Albendazole or praziquantel is indicated for inoperable and disseminated cases. Percutaneous aspiration, injection, and reaspiration (PAIR) technique is another nonsurgical option.